(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Three- to five-year-old children still have a need for affection, understanding and communication from adults. Confidence-based communication with adults and the ability to feel his emotional state (joy, pleasure, sadness, calmness, anger, etc.) and to understand the reasons for mood changes develop.